OPTIMIZATION OF SYAHFIRA BAKERY PRODUCTION USING THE TAGUCHI-PRINCIPAL COMPONENT ANALYSIS (PCA) METHOD - Dongoran, Rodiani; Dur, Sajaratud; Widyasari, Rina (Pena Cendekia Insani, 2022)
The bread-making business is part of the finished food industry which uses wheat flour as the main raw material for its production process. Bread production has quality characteristics, namely bread surface roughness (Smaller is better) and material processing rate (Larger is better). The combination of the Taguchi-Principal Component Analysis method is used to optimize bread products. The experimental design used is the L9 orthogonal matrix. These quality characteristics are influenced by factors such as the length of time for mixing and kneading, yeast fermentation, roasting time and the dose of water with 3 levels each. Principal Component Analysis (PCA) is used to eliminate correlated correlated responses to an uncorrelated quality index. The results showed that this method can improve the quality of bread production in influencing the surface roughness of the bread and the significant speed of processing the ingredients is the dough time, yeast fermentation, and baking time.